PENERAPAN KONSEP URBAN FARMING SEBAGAI USAHA KETAHANAN PANGAN DENGAN BERORIENTASI PADA FOOD ORIENTED DEVELOPMENT DI MASA PANDEMI COVID-19 BAGI MASYARAKAT DI DESA SUKAMAHI KECAMATAN SUKARATU KABUPATEN TASIKMALAYA - Yuniasih, Yuyun; Rosyadi, Agi; Kurniawati, Ane; Permana, Edi Ganda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
The concept of urban farming is here and offers a solution by creating and managing open land. In addition to getting closer to nature, urban farming can also strengthen social relations between its activists. When urban farming is applied in a neighboring environment, urban farming can strengthen a sense of togetherness and create a culture of mutual cooperation in the community, especially residential areas. Not only community empowerment activities, urban farming can also support the economic condition of the community itself through the marketing of their harvests as well as to support the Food Oriented Development launched by the government. This community service activity involves community groups in Sukamahi Sukaratu Village, Tasikmalaya Regency and coordinates with the local Village Apparatus. The methods used include (1) location surveys, (2) urban farming counseling to the community with communication, information methods, and (3) Focus Group Discussion (FGD) to produce an agreement with the community on the application of the urban farming concept through hydroponic techniques. Increasing knowledge and understanding of the community through the application of the concept of urban farming is very important as a solution to increase family income. Mutual agreement between the community and community leaders resulted in an agreement to utilize the yard by processing it into multipurpose land. Keywords: Urban Farming; Food Oriented Development; Community Economic Empowerment